Analisis Pencapaian Produktivitas Pemetikan Pucuk Sebagai Dampak Agrowisata Di Kebun Teh Gunung Mas, Bogor - Dahliani, Lili; Sudradjat; Arifin, Hadi Susilo (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2006)
The objective of the research was to study the impact of agro-tourism on production of tea bud. The experiment was conducted at Gunung Mas Tea Plantation, Bogor, from June 2004 to March 2005. Blocks 3, 5, 8, 10 and 17 at Gunung Mas I afdeling represented area with agro-tourism activity and blocks 3, 7, and 10 at South Cikopo I afdeling represented area without agro-tourism activity. Site selection was based on plant variety, age of cutting, tea walk track (0, 4, 6, and 10 km), and elevation height (800, 900, and 1000 m above sea level). The result shows that agro-tourism activity decreases production of tea bud. When the number of visitors increased, production of tea bud decreased because the pluckers were absent during the plucking time. The positive impacts of agro-tourism are improvement in plantation management, especially in productive plants, and existing additional income. Gunung Mas Tea Plantation especially Gunung Mas I afdeling which runs agro-tourism should limit the number of visitors and there must be a cross subsidy from agro-tourism to agro-industry sectors.   Key words :  Agro-tourism, productivity of tea shoots, afdeling, plucking.